Glucose-6-phosphate dehydrogenase deficiency, neonatal hyperbilirubinemia and Gilbert syndrome. - Costa, Elísio (2002)
The aim of this work was to evaluate the influence of abnormal UDP-glucoronosyltransferase-1 (UGT1A1) gene variant, on the incidence and severity of neonatal hyperbilirubinemia, in glucose-6-phosphate dehydrogenase (G6PD) deficient newborns. The A(TA)nTAA region in the promoter of the UGT1A1 gene was analysed in 20 children with G6PD deficiency. Fourteen of these children had the African type variant (G6PDA-) and 6 had different variants (G6PDNara, G6PDGuadalajara, G6PDDurham, G6PDTomah, G6PDAveiro e G6PDNashville) related to chronic nonspherocytic haemolytic anaemia (CNSHA). The existence of a positive history of neonatal hyperbilirubinemia, as well as its severity was registered. The incidence of neonatal hyperbilirubinemia was increased in this group of children (90%) and was not associated with abnormal alleles of the UGT1A1 gene. It was not possible to assess the influence of abnormal alleles in the severity of the neonatal hyperbilirubinemia. However, these abnormal alleles did not account for the severity of jaundice in children who presented variants related to CNSHA, since 5 were treated with an exchange transfusion and none presented abnormal alleles.